2007
DOI: 10.1016/j.jhse.2007.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Use of Modified Tension Band Sutures for Fingernail Disruptions

Abstract: A series of 66 patients, aged between 1 and 70 years, with 70 disruptive injuries to finger nails was reviewed. The injuries were treated by cleaning of the finger, evacuation of haematoma and anatomical replacement of the nail plate, or a substitute, which was secured with a modified dorsal tension band suture without formal repair of the nail bed. K-wire fixation of the distal phalanx was employed only in the event of displaced fracture of the distal phalanx, complete absence of the nail plate and laceration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
1
9
0
2
Order By: Relevance
“…Our results were comparable to Patankar's series that had only two deformed nails due to shortening secondary to comminuted nature of fractures. He used K-wires for fracture stabilization 18. We found that our results were also comparable to that of Bindra who used this technique in his series of 19 fracture lacerations of fingertips with 100% good results.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our results were comparable to Patankar's series that had only two deformed nails due to shortening secondary to comminuted nature of fractures. He used K-wires for fracture stabilization 18. We found that our results were also comparable to that of Bindra who used this technique in his series of 19 fracture lacerations of fingertips with 100% good results.…”
Section: Discussionsupporting
confidence: 80%
“…There are also reports of poor results following conventional nail bed repair 1617. Patankar (2007) in his series used this technique for nail bed injuries, and if there was associated fracture of distal phalanx, he used a longitudinal retrograde K-wire for fracture stabilization 18. Use of transverse figure-of-eight sutures for the fixation of the avulsed nail is also recommended by some authors 19…”
Section: Discussionmentioning
confidence: 99%
“…If the injury is proximal it may need additional procedures like two parallel K wire fixation or placing the nail plate as a splint and anchoring it with a figure of 8 suture to retain it in place. [24] [Figure 3]…”
Section: Types Of Injuriesmentioning
confidence: 99%
“…Kalın olmayan (0,7-0,8 mm'lik) teller kullanımına ve mümkünse DIP eklemin geçilmemesine dikkat edilir. [32,34] Şekil 6. a, b. Tırnak yaralanmasına eşlik eden ayrılmış distal falanks kırıkları olan olgularımızda 8 şeklinde gergi bandı vertikal sütür teknikleri: K-teli kullanıılmadığında (a) ve K-teli varlığında (b).…”
Section: Erişkinde Açık Tırnak Yatağı Yaralanması Ile Birlikte Olan unclassified
“…Tedavileri çekiç parmaktaki gibi en az altı hafta ekstansiyonda atellenmedir. [34] Bu konuda daha ayrıntılı bilgi yazının sonraki bölümünde yer almaktadır.…”
Section: (A) (B)unclassified